Faktor-Faktor yang Mempengaruhi Niat dan Keputusan Konsumen Membeli Sayuran dan Buah Secara Online - Esi Asyani Listyowati; Any Suryantini; Irham Irham (Jurnal Kawistara, 2020)
Compared to other goods, online trading on fresh agricultural products such as vegetables and fruit is still relatively new for the Indonesian people. What drives this growing interest in  purchasing  agricultural products online? This study aims to examine the factors influence consumers' intentions in purchasing vegetables and fruit online and further  analyzes the influence of purchase intentions on consumers’ decision to make the purchases online. The study was based on analysis of 146 users of online vetabales stores in various more than 10 online platfom accessible in Indonesia from July to August 2018. Users are aged from 15 to more than 54 years. Using seven exogenous latent variables predicted to influence purchase intentions, this study found four variables which proved to influence purchasing intentions, namely perceived usefulness, perceived price, income, and electronic word of mouth. Three variables were perceived ease of use, trust, and perceived risk prevention does not affect the purchase intention. The purchase intention as the first endogenous latent variable proved to influence consumer purchasing decisions as the second endogenous latent variable.